2020
DOI: 10.1111/sji.12897
|View full text |Cite
|
Sign up to set email alerts
|

Potential methods for improving the efficacy of mesenchymal stem cells in the treatment of inflammatory bowel diseases

Abstract: Inflammatory bowel diseases (IBD) are a group of chronic recurrent gastrointestinal inflammatory diseases, including ulcerative colitis (UC), Crohn's disease (CD) and IBD unclassified. The pathogenesis may be related to the mucosal immune dysfunction in genetically susceptible hosts affected by environmental factors. Current therapeutic agents mainly include aminosalicylates, corticosteroids, immunosuppressive drugs and novel biological agents. The purpose of treatment is to suppress inflammation and prevent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 98 publications
(117 reference statements)
0
10
0
Order By: Relevance
“…Although the protocol for the preparation of MSCs for this study was relatively simple and appeared to be safe and effective, there are many ways that cellular therapy can be influenced prior to infusion into a patient, and a number of adjustments to MSC treatment protocols (eg, donor selection, culture medium, dose, frequency and number of infusions and route of administration) that may enhance accessibility, efficacy and duration of effect, and require further investigation. 20,21…”
Section: Discussionmentioning
confidence: 99%
“…Although the protocol for the preparation of MSCs for this study was relatively simple and appeared to be safe and effective, there are many ways that cellular therapy can be influenced prior to infusion into a patient, and a number of adjustments to MSC treatment protocols (eg, donor selection, culture medium, dose, frequency and number of infusions and route of administration) that may enhance accessibility, efficacy and duration of effect, and require further investigation. 20,21…”
Section: Discussionmentioning
confidence: 99%
“…Actually, mesenchymal stem cells (MSCs) have shown safety as well as therapeutic significance in the field of regenerative medicine ( Mocchi et al, 2020 ). Currently, about 1,000 clinical trials worldwide have been reported to use MSCs to treat various diseases ( Pittenger et al, 2019 ; Kabat et al, 2020 ), including inflammatory and fibrotic diseases ( Ryu et al, 2020 ); liver disease ( Zhu et al, 2021 ), bone and joint diseases ( Li N. et al, 2020 ), inflammatory bowel diseases ( Zhang X. et al, 2020 ), diabetes ( Kuang et al, 2021 ), cardiovascular diseases ( Chen et al, 2021 ), neurodegenerative diseases ( Fayazi et al, 2021 ), spinal cord injuries ( Huang et al, 2021 ) and so on. Likewise, the emergence of cell-based therapies has also paved the way for utilizing MSCs in IVDD treatment.…”
Section: Mesenchymal Stem Cell-based Therapy In Ivdd Treatmentmentioning
confidence: 99%
“…These effects, in turn, maintain the intestinal integrity and support barrier function [25]. Noteworthy, current studies have shown that using the pre-conditioned MSCs [26,27] or MSCs-derived exosome [28,29], as an innovative cell-free approach, can be more favored strategy compared to naïve MSCs cells therapy. Modified MSCs or MSCs-derived exosomes could circumvent MSCs' low migration and engraftment to colon tissue, making them a rational and effective therapeutic strategy [30].…”
Section: Introductionmentioning
confidence: 99%